Use of alternative protein sources for finishing lambs. 2. Effects on chemical and physical characteristics and fatty acid composition of meat - Facciolongo, Anna Maria; De Marzo, Davide; Ragni, Marco; Lestingi, Antonia; Toteda, Francesco (Progress in Nutrition, 2015)
This study investigated the use of different protein sources (soybean, faba bean, sweet lupin and pea) in lamb feed and their influence on the chemical and physical characteristics of the meat and on the acid composition of intramuscular fat. The meat of lambs fed on faba bean contained a greater percentage of fat than those fed on lupin (P < 0.05) and soybean (P < 0.01). The meat of lambs fed on faba bean had a greater (P < 0.01) proportion of PUFA and a higher PUFA/SFA ratio than the meat of all other groups. The thrombogenicity index and nutritive value of meat fat were higher for lambs fed with faba bean and pea. The use of lupin in feed determined the highest (P < 0.01) SFA percentage, the lowest PUFA incidence and the worst thrombogenicity index. In conclusion, the protein sources studied did not influence the physical characteristics of the meat. However, the acid composition improved with the use of pea, and especially of faba bean.